HOUSEHOLD WASTE ANALYSIS IN REZEKNE CITY - Koļčs, Aigars; Noviks, Gotfrīds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The aim of the research work was to analyse the municipal solid waste management system in Rezekne city and to provide recommendations for it’s improvement. The work consists of 3 main chapters. The first chapter gives a short survey of information on waste management, on the type of waste treatment, waste stream management in Rezekne city. The second chapter reveals the methods used in the work. The third chapter gives the results of the work -reduction of the total number of waste to be disposed in landfill sites. At the end of the research work are given recommendations for improving the waste management system in Rezekne city.